Animal Conceptual Metaphors in Kotowaza: A Cognitive Linguistic Study - Iffatu Masrura Al Hakimi (Journal of Japanese Language Education and Linguistics, 2024)
The primary objective of this study is to examine the cognitive linguistic perspective of Japanese culture in relation to animal-related kotowaza. This study employs a qualitative descriptive approach to analyze 15 kotowaza from the comic book dictionary "Doraemon no Kotowaza Jiten." The objective is to determine the grammatical and idiomatic meanings of these kotowaza, as well as to comprehend the mental metaphor of animals present in them. The research findings suggest that Japanese society employs animal kotowaza as metaphors to convey implicit messages about an individual's character. The kotowaza conveys intricate messages regarding moral principles in everyday life, as well as a profound comprehension of flawed circumstances, through the use of conceptual analogies. Various animal metaphors, including fish, horse, bird, cat, and monkey, are employed to symbolize different facets of existence and human nature.